Where the cerebral infarction meets child, be vigilant about patent foramen ovale: a case report - Zhang, Zai-qiang; Ding, Jia-wang (Frontiers in Neurology, 2024)
Background: While cerebral infarction in children is rare, its prognosis is poor, and this condition can seriously burden society and families. A correlation between patent foramen ovale (PFO) and ischaemic stroke has not been found in paediatric patients. Case presentation: We report a 7-year-old boy who suffered from multiple cerebral infarctions. Subsequently, the patient was diagnosed with an abnormal shunt of PFO. He underwent PFO closure and was followed up for 1 year. The patient did not experience any further cerebral infarction. Conclusions: With this case report, we want to illustrate that although the incidence rate of ischaemic cerebral infarction in adolescents is very low, we should not neglect the role of PFO. Therefore, after exclusion other causes of cerebral infarction, PFO should be considered in adolescent and adult stroke patients with adult closure criteria in the same way.